Challenge and opportunity: Making sense of the 'first lockdown' experience of families with young children and health and social care practitioners in Southend-on-Sea (the United Kingdom). (May 2022) - Ioakimidis, Vasilios; O'Connell, Lauren; Baxter, Vanessa; Chard, Kathryn; Speed, Ewen; White, Gregory
COVID-19 has had a significant and measurable impact on individuals and families in economically deprived areas both in the United Kingdom and internationally. This article examines issues of community resilience and service adaptability and focuses on the period during the first lockdown in the United Kingdom (May to July 2020). Data were collected from members of the local community in Southend, with specific reference to the 'A Better Start Southend' programme of support. The evidence presented in this article uncovers the impact of the 'first lockdown' on families with young children, and local children's and community services.